Dry eye symptoms in interferon regulatory factor 3-deficient mice due to herpes simplex virus infection in harderian gland and lacrimal gland. (June 2022) - Zhu, Jing-Yi; Zhang, Xi; Zheng, Xiao; Luo, Lin-Lin; Mao, Cheng-Yi; Lin, Sen; Ye, Jian
Abstract: Purpose: Dry eye syndrome (DES) is a multifactorial ocular disorder. The possible pathogens and pathogenic mechanisms for virus-related dry eye disease are largely unknown. The current study aimed to provide evidence for mechanisms contributing to DES induced by herpes simplex virus (HSV) infection in the harderian gland (HG) and lacrimal gland (LG). Methods: We recorded the dry eye-like cornea pathology of irf3 −/− mice infected with HSV-1 till 8 months of age. The slit-lamp and confocal microscopy was used to observe the corneal defects. TUNEL was used to detect the corneal apoptosis. Human corneas suffered from herpes stromal keratitis (HSK) were also analyzed as a comparison. Then, we measure the aqueous tear production with a phenol red thread test in irf3 −/− mice, and recorded their tear film breakup time. HGs and LGs were sectioned and analyzed using HE and oil-red-O staining. For molecular signaling pathway analysis, we used mRNA sequencing to explore the related gene ontology. Western blotting (WB) and real-time reverse transcription-quantitative polymerase chain reaction were used to verify the level of the Akt signaling pathway and related inflammatory factors. Results: Inoculated irf3 −/− mice tended to develop dry eye-like symptoms, such as corneal keratinization, corneal cell apoptosis, and tear reduction. The HGs and LGs of irf3 −/− mice showed increased level of HSV-1, and exhibited inflammatory pathological changes and impaired function, which explained the damaged tear film. WB and mRNA sequencing indicated that enhanced PI3K-Akt pathway in irf3 −/− mice might account for the higher susceptibility to HSV infection. Conclusions: We observed evidence of DES in irf3 −/− mice induced by HSV-1 infection in the HGs and LGs, which may introduce a potential novel target for DES treatment. Highlights: HSV-1 inoculated IRF3-deficient mice had dry eye symptoms. Corneal keratinization was sex-dependent and age-dependent in irf3−/− mice. HSV infection in the lacrimal and harderian glands contributes to the impaired tear secretion function. PI3K-Akt signaling pathway was screened and involved in the HSV infection in harderian gland.